Examining female leadership in the workplace through a comparison of French and Czech professional experiences - Slánská, Natálie (2024)
This thesis examines the leadership of women in the workplace through a comparative analysis of French and Czech professional experiences. The aim of the study is to identify the main obstacles and challenges that make it difficult for women to advance to leadership positions in these two different socio-cultural contexts. Using theoretical frameworks and empirical research, the thesis explores cultural dimensions, legal and policy frameworks, gender diversity and gender pay gaps. Through semi-structured interviews with female executives in both countries and the study of existing reports from top companies in the food industry, the research provides insights into the effectiveness of gender quotas, affirmative action and policies that promote work-life balance. The findings reveal important cultural and organizational differences that affect women's opportunities in leadership positions and suggest strategies to increase gender diversity in leadership positions in France and the Czech Republic and to facilitate the work-life balance of women leaders. This work contributes to a deeper understanding of the systemic factors affecting women's career advancement and offers practical recommendations for promoting gender equality in leadership positions.